Integrity as the Goal of Character Education. (October 2022) - Webber, Jonathan
Abstract: Schools and universities should equip students with the ability to deal with an unpredictable environment in ways that promote worthwhile and fulfilling lives. The world is rapidly changing and the contours of our ethical values have been shaped by the world we have lived in. Education therefore needs to cultivate in students the propensity to develop and refine ethical values that preserve important insights accrued through experience while responding to novel challenges. Therefore, we should aim to foster the virtue of ethical integrity. This virtue is driven by a concern for ethical accuracy, which motivates and warrants respect for our existing ethical commitments as repositories of previous ethical reasoning, but equally requires recognition of our own fallibility and consideration of other people's reasoning. Ethical integrity thus comprises constancy, fidelity, humility, and receptivity, balanced and integrated by the aim of ethical accuracy. It is a kind of ethical seriousness, though it includes acceptance of some degree of ambivalence. It is an inherently developmental virtue distinct from the unachievable ethical perfection of practical wisdom. It is an Aristotelian virtue, even though Aristotle does not himself name it. The paper closes with an outline of what education for ethical integrity would look like.